Approximate analytical solution of linear and nonlinear fractional delay differential equations using new variational iteration method - Srivastava, Vineet (Open Science Journal, 2020)
In this paper, an approximate analytical method, New Variational Iteration Method (NVIM) is introduced in this paper for the approximate analytical solution of Fractional Delay Differential Equations (FDDE). The algorithm is illustrated by studying initial value linear and nonlinear problems. The results obtained are presented and show that only few terms are required to get an approximate solution.